A new species of flea-toad of the genus Brachycephalus Fitzinger, 1826 (Anura: Brachycephalidae) from the cloud forests of Serra do Mar, southeastern Brazil. - Nunes, Ivan [UNESP]; Lyra, Mariana Lúcio [UNESP]; Machado, Thaynara M; Carrasco-Medina, Andres Santiago; Andrade, Felipe Silva DE; Haga, Isabelle Aquemi; Botelho, Lucas M; Pedrozo, Mariana; Velasco, Isabel Gonzalves [UNESP]; Jacinavicius, Fernando DE Castro; Gray, Jaimi A; Blackburn, David C; et al. (Magnolia Press, 2025)
Species of the genus Brachycephalus are endemic to the Brazilian Atlantic Forest, where they inhabit amidst the leaf litter. Depending on their phenotypic traits, these small-sized amphibians are commonly referred to as either flea-toads or pumpkin toadlets. Among them, the pumpkin toadlets (with a bufoniform phenotype) have received more extensive research attention. These individuals are often conspicuous, and prevalent in their natural habitat. In contrast, the flea-toads (leptodactyliform species) are brownish, cryptic with the background. This scarcity has led to their reduced scientific attention, including in the realm of taxonomy. Thus, we herein describe a new species of the genus Brachycephalus from montane forests of the Estao Ecolgica de Bananal, in the municipality of Bananal, state of So Paulo, Brazil. The new species is characterized by having a leptodactyliform body; adult SVL 6.99.0 mm for males and 9.29.6 mm for females; smooth skin lacking hyperossification; snout rounded in dorsal view; finger II with pointed tips; toe I absent (lacking phalanges), and toes II, III, IV and V distinct; toe II with rounded tips; brown background with few golden spots scattered aleatory in the general coloration of dorsal surfaces and cloacal region; presence of a dark brown stripe along the flanks and the thigh; yellow blotches on the ventral surfaces; presence of dark brown strips on the legs. Based on molecular phylogeny, we recognize the Brachycephalus puri species group, based on a clade composed by B. puri sister to the new species plus a candidate new species. The new species probably has a restricted geographic distribution, and its discovery reinforces the importance of deeper taxonomic effort with the brownish leptodactyliform species of the genus.